Assessment of the Effectiveness of Investment in R&D by European Union Countries - Romualdas Ginevičius (Amfiteatru Economic)
Investment in R&D today is an essential condition for the economic development of companies, industry as a whole and countries and regions. On the other hand, the financial capacity of economic operators is limited and it is important to know the benefits of these investments. In this context, the problem of their effectiveness is of particular importance. An adequate picture is provided by the analysis of the overall R&D process and its components – the impact on the creation of new knowledge; the impact of the new knowledge expressed in patents on the investment; the impact of innovation on the country’s economic development. The study highlighted the following patterns: The developed countries of the European Union are characterised by higher R&D investment compared to developing countries, a significantly higher number of patent applications and the higher Global innovation index values. A different picture is with the effectiveness of R&D investment. Both patents and the entire investment processes are more efficient in the developing countries. This is due to a significant increase in patent sales in developed countries, a more decentralized innovation policy, i.e. significantly higher exports to other countries. All this distorts the picture of the actual effectiveness of R&D investments.